Seriously Ill Patients’ Prioritized Goals and Their Clinicians’ Perceptions of Those Goals - Modes, Matthew E.; Engelberg, Ruth A.; Nielsen, Elizabeth L.; Brumback, Lyndia C.; Neville, Thanh H.; Walling, Anne M.; Curtis, J. Randall; Kross, Erin K. (Journal of pain and symptom management, 2022)
Seriously ill patients whose prioritized healthcare goals are understood by their clinicians are likely better positioned to receive goal-concordant care. To examine the proportion of seriously ill patients whose prioritized healthcare goal is accurately perceived by their clinician and identify factors associated with accurate perception. Secondary analysis of a multicenter cluster-randomized trial of outpatients with serious illness and their clinicians. Approximately two weeks after a clinic visit, patients reported their current prioritized healthcare goal- extending life over relief of pain and discomfort, or relief of pain and discomfort over extending life - and clinicians reported their perception of their patients’ current prioritized healthcare goal; matching these items defined accurate perception. Of 252 patients with a prioritized healthcare goal, 60% had their goal accurately perceived by their clinician, 27% were cared for by clinicians who perceived prioritization of the alternative goal, and 13% had their clinician answer unsure. Patients who were older (OR 1.03 per year; 95%CI 1.01, 1.05), had stable goals (OR 2.52; 95%CI 1.26, 5.05), and had a recent goals-of-care discussion (OR 1.78, 95%CI 1.00, 3.16) were more likely to have their goals accurately perceived. A majority of seriously ill outpatients are cared for by clinicians who accurately perceive their patients’ prioritized healthcare goals. However, a substantial portion are not and may be at higher risk for goal-discordant care. Interventions that facilitate goals-of-care discussions may help align care with goals, as recent discussions were associated with accurate perceptions of patients’ prioritized goals.